Gandhian Model of World Peace: Exploring the effectiveness of Gandhian approach to achieving world peace (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Longing for peace has never been so profound as it is nowat the threshold of the new millennium when the entire humankind is sitting onthe powder keg of huge stockpiles of sophisticated nuclear and other weapons ofmass destruction. Apart from the nuclear weapons, - equally terrible prevalentdiseases like AIDS, Cancer, SARS etc. are wide spread in different parts of theglobe posing serious threat to humanity. Apart from these, wars, regionalconflicts, terrorism, exacerbation in violence etc. are other dangers thatthreaten humanity. Thus, at almost all levels, the world is in the grip ofeither real or potential conflicts. In order to free the world from the stateof conflict situations, several formulas and theories and techniques such asthe Balance of Power Model, Global Centralism Model, the Marxist Model! theRevolutionary Model, and the Structural Model etc. have come up in the recentpast. Initially these theories gained wide recognition and support, especiallyin the West and efforts have also been made to put them into practice. Butstill, "international conflicts have increased both in number and in theirdimensions"[1],thereby proving the futility of these theories/models to measure up to thechallenge. [1]               Manish Sharma, "GandhianApproach to Peace", in Anil Dutta Mishra (ed.),                Challenges of the 21st Century, MittalPublications, New Delhi, 2003, p. 339.